2002
DOI: 10.1002/yea.911
|View full text |Cite
|
Sign up to set email alerts
|

A cell surface display system using novel GPI‐anchored proteins in Hansenula polymorpha

Abstract: A cell surface display system was developed in yeast Hansenula polymorpha.The four genes HpSED1, HpGAS1, HpTIP1 and HpCWP1, encoding glycosylphosphatidylinositol (GPI)-anchored cell surface proteins from H. polymorpha, were cloned, characterized and evaluated for their efficacies as cell surface display motifs of reporter proteins. Sequence analysis of these genes revealed that each encodes a typical GPIanchored protein that is structurally similar to a counterpart gene in S. cerevisiae. The genes showed a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…To further test our cell membrane hypothesis we weakened the cell wall by inhibiting chitin biosynthesis using the chitin synthase inhibitor NKZ, which has been shown to inhibit all three Chs isozymes in C. albicans , and in turn results in a lack of chitin in fungal cells (Kim et al, 2002). We reasoned that if the membrane were the active target then the weakened cell would become hyper-susceptible to CHD-FA.…”
Section: Discussionmentioning
confidence: 99%
“…To further test our cell membrane hypothesis we weakened the cell wall by inhibiting chitin biosynthesis using the chitin synthase inhibitor NKZ, which has been shown to inhibit all three Chs isozymes in C. albicans , and in turn results in a lack of chitin in fungal cells (Kim et al, 2002). We reasoned that if the membrane were the active target then the weakened cell would become hyper-susceptible to CHD-FA.…”
Section: Discussionmentioning
confidence: 99%
“…DNA sequencing was carried out with an automatic DNA sequencer (ABI model 373A; Applied Biosystems). The plasmid pGA-GOD-CwpF (15) contained the GAPDH (glyceraldehyde-3-phosphate dehydrogenase) gene promoter (27), HARS36 for autonomous replication (28), the LEU2 gene of H. polymorpha (2), and CwpF as a surface display anchor from H. polymorpha (15). This plasmid was used as a backbone for construction of a Candida antarctica lipase B (CALB) expression vector.…”
Section: Strains and Mediamentioning
confidence: 99%
“…H. polymorpha is also a useful biocatalyst for metabolic pathway engineering in which expression of multiple genes in different ratios is necessary (8). Recently, a surface display system in H. polymorpha using novel cell wall proteins was developed (15). Surface display plays an important role in linking the genotype and phenotype in directed evolution of useful proteins.…”
mentioning
confidence: 99%
“…Although cell surface display using TIP1p in Hansenula polymorpha was reported (Kim et al 2002), there are no reported studies in P. pastoris yet. Here we report the results of surface display of hLf using ScTIP in P. pastoris.…”
Section: Introductionmentioning
confidence: 98%